Снижение вероятности ложной тревоги при тепловом неразрушающем контроле сотовых конструкций - Мягкий, А. В. (ХНУРЭ, 2012)
In this work the thermal-physical model of the starved spots in the honeycomb sandwich detection process was considered. The interferences caused by an emissivity fluctuation and a glue film inhomogeneity suppression way based on corresponding technique of data processing choice was suggested
Keywords: thermal-physical model; физика